2009
DOI: 10.1188/09.onf.e47-e56
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Strategies to Cope With Taste Changes After Chemotherapy

Abstract: Mary Lappe, RN, BSN, OCN® [Oncology nurse clinician]Oncology Specialists, S.C AbstractPurpose/Objectives-To describe factors related to taste changes, to examine patients' use of a self-care suggestion sheet to manage taste changes associated with chemotherapy, and to identify potentially useful strategies for managing specific taste changes after chemotherapy.Design-Quasi-experimental, pre/post design. Setting-Four outpatient urban and suburban oncology centers in Illinois.Sample-42 patients who had received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 30 publications
(41 reference statements)
1
69
0
8
Order By: Relevance
“…Previous studies have shown a prevalence of metallic taste in cancer patients treated with chemotherapy ranging from 10% to 78% (16)(17)(18)(19)(20)(21)(22). Also, metallic taste in patients treated with radiotherapy has been reported previously (23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a prevalence of metallic taste in cancer patients treated with chemotherapy ranging from 10% to 78% (16)(17)(18)(19)(20)(21)(22). Also, metallic taste in patients treated with radiotherapy has been reported previously (23).…”
Section: Discussionmentioning
confidence: 99%
“…Seven out to 12 studies used previously studied, validated standardized tool to find out the taste change and improvement; four of them used objective, close ended questions to find out the improvement with a given treatment or strategy. Most of the studies included patients with chemotherapy, [20,26,[30][31][32][33][34][35] some of the studies were confined to radiotherapy, [3,24,28] and a few studied the patients receiving a combination of treatment. [29] Amongst these, the most common chemotherapeutic agent was carboplatin and oxyplatin but, most of them used various chemotherapeutic agents.…”
Section: Resultsmentioning
confidence: 99%
“…[3,20,26,27] Two studies were cross sectional studies, [30,31] and there were three prospective longitudinal studies, [32][33][34] one was a case study, [34] and another one quasi experimental study. [35] Sample size ranged from two to 531, with commonest diagnosis of head and neck cancer followed by breast cancer, lung cancer, gastrointestinal (GI) cancer, and a wide range of other cancer diagnosis. Seven out to 12 studies used previously studied, validated standardized tool to find out the taste change and improvement; four of them used objective, close ended questions to find out the improvement with a given treatment or strategy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations